(untitled) (Research, Society and Development, 2021)
Humans developed a symbiotic relationship with their gut microbiota, a complex microbial community made up of bacteria, archaea, protists and viruses, including bacteriophages. The enteric nervous system (SNE) is a gateway to bidirectional communication between the brain and the intestine, mainly through the vagus nerve (VN). Therefore, environmental exposure plays a fundamental role in both the composition and functionality of the intestinal microbiome and can contribute to susceptibility to neurodegenerative disorders, such as Parkinson’s disease (PD). This is a systematic review of the literature using the data bases PUBMED, Scielo and MEDLINE, using the descriptors present in the Health Sciences Descriptors (DeCS): Parkinson’s disease, cytokines, microbiota and gastrointestinal tract. It can be mentioned that the neuropathological characteristic of PD is the generalized appearance of alpha-synuclein (α-Syn) aggregates in the central and peripheral nervous systems, including the SNE. Many studies suggest that intestinal toxins can induce the formation of α-Syn aggregates in the SNE, which can then be transmitted to the CNS via the VN. PD is strongly associated with aging and its negative effects on homeostatic mechanisms that protect against inflammation, oxidative stress and protein malfunction. Thus, this study intends to carry out, based on analyzes of inflammatory cytokines and intestinal microbiota, how dysbiosis can contribute to the onset or complications of PD, promoting a correlation between clinical and laboratory manifestations and prognosis, as well as describing the main mechanisms causal factors that are still poorly understood.